2002
DOI: 10.1177/0148607102026006372
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prebiotics on the immune response to vaccination in the elderly

Abstract: No immunological effects of prebiotics were observed in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 24 publications
9
66
0
2
Order By: Relevance
“…However, the percentage of activated T cells (defined as CD3 þ HLA-DR þ ) increased while that of NK T cells (defined as CD3 þ NK þ ) decreased (64) . This mixed picture of effects of b2-1 fructans on blood lymphocyte subsets is similar to that seen in laboratory animals (48,49) .Lymphocyte proliferation to influenza vaccine components was increased in elderly adults supplemented with FOS (62) , but in another study in elderly adults, there was no effect of (60) . Regarding cytokine expression, in elderly nursing home residents, OF supplementation decreased IL-6 mRNA expression in blood mononuclear cells (24) , and in elderly adults resident in long-term care facilities, IL-6 production by stimulated blood mononuclear cells was decreased (63) .…”
supporting
confidence: 72%
See 2 more Smart Citations
“…However, the percentage of activated T cells (defined as CD3 þ HLA-DR þ ) increased while that of NK T cells (defined as CD3 þ NK þ ) decreased (64) . This mixed picture of effects of b2-1 fructans on blood lymphocyte subsets is similar to that seen in laboratory animals (48,49) .Lymphocyte proliferation to influenza vaccine components was increased in elderly adults supplemented with FOS (62) , but in another study in elderly adults, there was no effect of (60) . Regarding cytokine expression, in elderly nursing home residents, OF supplementation decreased IL-6 mRNA expression in blood mononuclear cells (24) , and in elderly adults resident in long-term care facilities, IL-6 production by stimulated blood mononuclear cells was decreased (63) .…”
supporting
confidence: 72%
“…In the same study, there was no effect of the combination of OF and IN upon salivary secretory IgA levels (60) . In newborn infants supplemented with a mixture of GOS and IN with shorter-chain FOS removed in their formula, an increase in faecal secretory IgA levels was seen (65) , which fits with the findings from animal studies which show an enhancement of the antibody response in the GALT by prebiotics (47,49,51 -53) .…”
Section: Of Nk Cells † Numbers Of Activated T Cells (Cd25)mentioning
confidence: 78%
See 1 more Smart Citation
“…In a later study by the same research group, these changes in immune parameters were confirmed with supplementation of 2-4 g/day FOS for 12 weeks in a group of older persons at risk of malnutrition (Schiffrin et al, 2007). Bunout et al (2002) investigated the effect of prebiotics on the response to vaccination in elderly. A mixture of inulin and oligofructose (70/30; 6 g/day) did not lead to a changed immunological response in the volunteers aged 470 y.…”
Section: Immune Modulation In Infantsmentioning
confidence: 99%
“…For example, studies indicate that test prebiotics could reduce production of proinflammatory cytokines IL-6 and TNF-␣ in elderly people [28,70,82]. However, in one study, oligofructose/inulin supplemented with vitamins and protein did not show immuno-regulatory effects in elderly persons [83]. Probiotics may also modulate the immune system of elderly people e.g., L. rhamnosus HN001 [84][85][86][87] and B. lactis HN019 [86,[88][89][90] are well studied strains.…”
Section: Effects On Immune Functionmentioning
confidence: 97%